2020
DOI: 10.3390/cancers12092448
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Cationic Amphiphilic Helical Peptidomimetic (B18L) As A Novel Anti-Cancer Drug Lead

Abstract: BST-2 is a novel driver of cancer progression whose expression confers oncogenic properties to breast cancer cells. As such, targeting BST-2 in tumors may be an effective therapeutic approach against breast cancer. Here, we sought to develop potent cytotoxic anti-cancer agent using the second-generation BST-2-based anti-adhesion peptide, B18, as backbone. To this end, we designed a series of five B18-derived peptidomimetics. Among these, B18L, a cationic amphiphilic α-helical peptidomimetic, was selected as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…A.M. Yu, UC Davis. The tamoxifen (TAM) resistant lines were maintained in MCF7 base media supplemented with 1 μM or 5 μM TAM [44]. The mitoxantrone resistant line (MX-100) was maintained as previously described [45].…”
Section: Methodsmentioning
confidence: 99%
“…A.M. Yu, UC Davis. The tamoxifen (TAM) resistant lines were maintained in MCF7 base media supplemented with 1 μM or 5 μM TAM [44]. The mitoxantrone resistant line (MX-100) was maintained as previously described [45].…”
Section: Methodsmentioning
confidence: 99%
“…Percentage of viable cells was inferred by quantitation of cellular ATP, measured using CellTiter-Glo Luminescent viability assay [ 61 , 62 ].…”
Section: Methodsmentioning
confidence: 99%
“…Thus, targeting BST-2 may be a versatile option for the treatment of breast cancer patients (Mahauad-Fernandez and Okeoma 2018 ). As the backbone of their cytotoxic anti-cancer agent, Yuan Lyu et al ( 2020 ) used the BST-2 anti-adhesion peptide B18, a second-generation anti-adhesion peptide against BST-2. They designed five peptidomimetics based on B18.…”
Section: New Opportunity Of Peptidomimetic For Cancer Drug Resistancementioning
confidence: 99%
“…5 ). Studies on B18L have shown that this peptidomimetic decreases Src and Erk1/2, enhances Bcl2 pro-apoptotic proteins, and triggers caspase bed processing in breast cancer (Lyu et al 2020 ).
Fig.
…”
Section: New Opportunity Of Peptidomimetic For Cancer Drug Resistancementioning
confidence: 99%